Cane toad (Rhinella marina) vitamin A, vitamin E, and carotenoid kinetics. Issue 1 (29th August 2021) - Freel, Tarra; Koutsos, Elizabeth; Minter, Larry J.; Tollefson, Troy; Ridgley, Frank; Smith, Dustin; Scott, Heather; Ange‐van Heugten, Kimberly
Abstract: Many amphibian species are threatened with extinction. Understanding their vitamin A (retinol), E (alpha‐tocopherol), and carotenoid requirements is vital, as normal levels of these nutrients have a known connection to breeding success with abnormal levels leading to disease. This research examined vitamins A, E, and carotenoids (apocarotenoid, beta‐carotene; beta‐cryptoxanthin, lutein, zeaxanthin, and esters) concentration kinetics in the liver and plasma of 65 (57.8) cane toads ( Rhinella marina ) over 4 months supplemented with commercially available invertebrates in human care. Cane toads were opportunistically collected as part of a population control program for use as an amphibian model species. Toads were randomly assigned to one of two diets: treatment 1 was brown house crickets ( Acheta domesticus ) consuming Mazuri® Hi Calcium Gut Loading Diet without vitamin A or E supplement, plus fresh raw vegetables (carrot/sweet potato); Treatment 2 was the same diet except no vegetables. Ten toads were euthanized on Day 0 to analyze baseline free‐ranging liver and plasma metabolites. Six toads consuming each treatment were euthanized on Days 22, 50, and 81, and n = 7 on Day 119 for analysis. Regardless of dietary treatment, most liver and blood metabolites were substantially higher at time 0 than all time points thereafter ( p < .05); Ex: liver vitamin A at time 0 was 87.7 ± 16.12 µg/g while Day 119 for treatments 1 and 2 were 11.6 ± 1.19 and 8.2 ± 0.74, respectively. Few statistically significant differences between diets at the same time point were noted ( p < .05). The results from this study indicate that additional or alternative diet supplementation may be needed for cane toads (and potentially other amphibians) to mimic their free‐ranging diets. Abstract : Vitamins A, E, and carotenoids (β‐carotene as shown) in the liver of cane toads decreased dramatically from time 0 (wild) through 120 days consuming diets within human care ( p < .05). RESEARCH HIGHLIGHTS: Vitamins A, E, and carotenoids in the liver and plasma of cane toads ( Rhinella marina ) were higher at time 0 (wild caught) than all‐time points after ( p < .05). Diet supplementation may be needed for cane toads to mimic their free‐ranging diets.